Effects of rye and triticale seed proteins on Leptinotarsa decemlineata (Say) digestive α-amylase and protease and some biological parameters. (1st October 2016) - Ashouri, Shabnam; Farshbaf Pourabad, Reza; Bandani, Alireza; Fatehi, Soheyla
Abstract: The current study aimed to investigate the effect of rye and triticale seed proteins on the Leptinotarsa decemlineata, gut enzymes. Results showed that ammonium sulphate precipitation fractions; 0–30, 30–50, 50–70 and 70–100% had no inhibition on the fourth instar larval (L4 ) protease activity, while first two fractions of triticale and all fractions of rye had inhibitory effects on the all larval stages and adult's α-amylase activity. Mode of inhibition in rye and triticale was partial mixed and uncompetitive, respectively. Zymograms approved the results. Feeding assays were conducted using four cultivars of potato leaves treated with extracts. Weight of L4 on Marx in both trials and the L4 evolution in all cultivars in rye and just on Picasso in triticale were reduced, the developmental durations were increased on Marx and Picasso in triticale trial significantly. Also, rye extract caused inhibition in amylase activity of survived individuals that feed from treated Burren leaves.